Can a woman travel as a woman? Perceptions of travel barriers to women by personality trait - Tanrısever, Canan; Karaset, Ş. Buse; Koç, Dilara Eylül (Turyzm/Tourism, 2023)
The aim of this study is to examine differences in women’s perceptions of travel constraints by personality trait, according to age, educational level, personal income, travelled destination, the purpose of travelling, the time spent travelling, the region travelled to and the factors that affect the choice of destination. The survey data collected from a sample of 304 women travellers were analyzed by performing one-way analysis of variance (ANOVA). The results showed that there are significant differences between women’s perceptions of travel constraints and personal income, the region they travelled to and the purpose of travelling. Significant differences between women’s personality traits and age, education level, duration of travel, destination and destination choice were also found.